Heat stress assessment stakeholder consultation in Zambia - Mutua, John Y.; Sikaceya, Noah (2021)
Increases in temperature and humidity caused by climate change will cause heat stress and this is expected to have an influence on the East African dairy industry. Zambia is already experiencing moderate heat stress conditions and predictions point to the possibility of severe conditions in the future. This indicates that production-specific heat-stress adaptation techniques for enhancing heat tolerance are urgently needed for future dairy industry productivity in Zambia, as demand for animal products including milk and other dairy products is expected to rise in the country. Considering the heat stress mapping study for several livestock species conducted previously, the CGIAR Research Program on Livestock conducted an adaptation-planning workshop in Zambia under the auspices of the GIZ funded project “Towards climate-resilient dairy production in Southern Zambia”.